2018
DOI: 10.1128/mbio.02443-17
|View full text |Cite
|
Sign up to set email alerts
|

An Autocrine Proliferation Repressor Regulates Dictyostelium discoideum Proliferation and Chemorepulsion Using the G Protein-Coupled Receptor GrlH

Abstract: In eukaryotic microbes, little is known about signals that inhibit the proliferation of the cells that secrete the signal, and little is known about signals (chemorepellents) that cause cells to move away from the source of the signal. Autocrine proliferation repressor protein A (AprA) is a protein secreted by the eukaryotic microbe Dictyostelium discoideum. AprA is a chemorepellent for and inhibits the proliferation of D. discoideum. We previously found that cells sense AprA using G proteins, suggesting the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 34 publications
3
36
0
Order By: Relevance
“…We previously observed that AprA binds to the G-protein–coupled receptor GrlH, requires GrlH and the G protein Gβ to inhibit proliferation and to induce chemorepulsion, and uses the G protein Gα8 to inhibit proliferation (Bakthavatsalam et al. , 2009; Phillips and Gomer, 2012; Tang et al. , 2018).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously observed that AprA binds to the G-protein–coupled receptor GrlH, requires GrlH and the G protein Gβ to inhibit proliferation and to induce chemorepulsion, and uses the G protein Gα8 to inhibit proliferation (Bakthavatsalam et al. , 2009; Phillips and Gomer, 2012; Tang et al. , 2018).…”
Section: Resultsmentioning
confidence: 99%
“…The beginning of the cAMP chemoattraction pathway involves a G protein–coupled receptor activating G proteins and Ras, and AprA uses the G protein–coupled receptor GrlH, and the G proteins Gα8 and Gβ (Phillips and Gomer, 2012; Tang et al. , 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cells lacking AprA proliferate faster than wild type cells, whereas overexpression of AprA or the addition of recombinant AprA to cultures modestly slows, but does not stop, proliferation . In the extracellular environment, AprA forms a complex with a protein called CfaD (Choe et al, 2009, Tang et al, 2018. In addition to slowing proliferation, AprA acts as a chemorepellent for vegetative cells (Phillips and Gomer, 2012).…”
Section: Chemorepulsion Away From Apramentioning
confidence: 99%
“…As with the chemoattractants cAMP and folic acid, AprA is sensed by a G protein coupled receptor called GrlH (Tang et al, 2018). As with chemoattraction to cAMP, AprA also induces Ras activation, and Ras activity is required for AprA-induced chemorepulsion (Rijal et al, 2018).…”
Section: Chemorepulsion Away From Apramentioning
confidence: 99%